Combining frequency-difference and ultrasound modulated electrical impedance tomography. (6th August 2015) - Harrach, Bastian; Lee, Eunjung; Ullrich, Marcel
Abstract: Electrical impedance tomography (EIT) is highly affected by modeling errors regarding electrode positions and the shape of the imaging domain. In this work, we propose a new inclusion detection technique that is completely independent of such errors. Our new approach is based on a combination of frequency-difference and ultrasound modulated EIT measurements.